2017
DOI: 10.1002/cncy.21926
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive follicular thyroid neoplasm with papillary‐like nuclear features (NIFTP): Implications for the risk of malignancy (ROM) in the Bethesda System for Reporting Thyroid Cytopathology (TBSRTC)

Abstract: The institutional frequency of NIFTP histopathology diagnosis and cytology baseline data will impact the ROM associated with specific FNAC diagnoses, especially among the indeterminate TBSRTC categories. The range of ROM for each TBSRTC diagnostic category is reflective of the inherent diagnostic thresholds and interobserver and interinstitutional variability in the diagnosis of thyroid lesions. Cancer Cytopathol 2018;126:20-6. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 33 publications
2
69
0
Order By: Relevance
“…Patients with indeterminate nodules that undergo surgical resection often turn out to have benign thyroid nodules or only indolent neoplasms, including NIFTP. NIFTP includes cases of indeterminate FNA previously diagnosed on histopathology as FVPC . The discrimination between benign and malignant thyroid lesions often requires documentation of vascular and capsular invasion, which cannot be established by cytological evaluation alone.…”
Section: Molecular Profiling Of Thyroid Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with indeterminate nodules that undergo surgical resection often turn out to have benign thyroid nodules or only indolent neoplasms, including NIFTP. NIFTP includes cases of indeterminate FNA previously diagnosed on histopathology as FVPC . The discrimination between benign and malignant thyroid lesions often requires documentation of vascular and capsular invasion, which cannot be established by cytological evaluation alone.…”
Section: Molecular Profiling Of Thyroid Lesionsmentioning
confidence: 99%
“…Noninvasive encapsulated follicular variant of papillary thyroid carcinoma (NE‐FVPTC) was recently reclassified as NIFTP . As shown in the second edition of the Bethesda thyroid system, this new terminology has decreased the ROM in most of the TBSRTC categories, most significantly in the indeterminate categories . Some studies have demonstrated that NIFTP can indeed be differentiated from PTC in cytological samples .…”
Section: Niftp and Molecular Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of all the changes related to the NIFTP reclassification apparently depends on the incidence of NIFTP in a certain population. Approximately, 30 studies have been conducted in America, Europe and Asia reporting variable incidence . Bychkov et al, in a meta‐analysis, documented an average worldwide prevalence rate of 9.1%, with a lower rate in Asian studies (1.6%) as compared with non‐Asian countries (13.3%) .…”
Section: Discussionmentioning
confidence: 99%
“…less frequent than in adults. 10 Medullary, poorly differentiated and anaplastic thyroid cancer are very rare in childhood.…”
Section: Epidemiologymentioning
confidence: 99%